Investigating the relationship between religious orientation and spiritual intelligence with general health dimensions in women with breast cancer - Mahnaz Noroozi; Zahra Mohebbi-Dehnavi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Breast cancer is the most common type of cancer and the second leading cause of death among women. Religion and spiritual behaviors are effective strategies for maintaining human health. The aim of this study was to determine the relationship between religious orientation and spiritual intelligence with general health dimensions in women with breast cancer. MATERIALS AND METHODS: The present study is a correlational study that was performed on 50 women with breast cancer referred to medical centers affiliated to Isfahan University of Medical Sciences in 2020. Data were collected through questionnaires of religious orientation, spiritual intelligence, and general health. Data were analyzed by Spearman and regression tests. RESULTS: The results showed that religious orientation had a significant positive relationship with the overall score of general health, but the components of religious orientation had a significant negative relationship with the number of components of public health (p < 0.05). Spiritual intelligence also had a significant positive relationship with general health. However, the number of components of spiritual intelligence has a significant negative relationship with the number of components of general health (p < 0.05). CONCLUSION: Considering the relationship between religious orientation and spiritual intelligence with public health and considering educational programs based on spiritual intelligence and religious orientation in this group of people can be an important step in promoting their general health.